Exploring the Nutritional Value and Health Benefits of Honey from the Portuguese Protected Area of Montesinho Natural Park - Clara Grosso; Sónia Soares; Aurora Silva; Cristina Soares; Manuela M. Moreira; Olena Dorosh; M. Fátima Barroso; Miguel A. Prieto; Cristina Delerue-Matos (Foods)
The main objective of this study was to provide an overview of the potential health-promoting properties of honeys collected at specific apiary locations from the protected area of Montesinho Natural Park (MNP), by analyzing their amino acid and polyphenolic profiles, and their biological properties, and comparing them with the renowned Manuka honey. The results revealed differences in total phenolic content among the samples examined and between sampling campaigns, with values ranging from 55.6 to 225 mg gallic acid equivalents (GAE) per 100 g of honey, compared to 57.2 mg GAE/100 g for Manuka honey. Gallic acid, neochlorogenic acid, and catechin were the key phenolics of MNP honey samples. MNP honey exhibited high levels of essential amino acids (phenylalanine, lysine, and valine), strong antioxidant and antimicrobial activities, moderate enzyme inhibition, and high proline content in some locations. These results highlight the exceptional nutritional and therapeutic potential of MNP honey.